Strategi Pengembangan Usaha Bibit Ikan Lele Ditinjau Dari Perspektif Ekonomi Islam (Studi Kasus Di Kabupaten Tanggamus) - Saputra, Ridwan Gilang Aji; Komariah, Rizka; Umar, M Abdullah (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2023)
In the business world, marketing is an integral part. However, in sharia marketing, the entire process must be in accordance with the contracts and principles of muamalah in Islam.  The development of the catfish seedling business in Tanggamus Regency still has several challenges that need to be overcome. To overcome these challenges, an appropriate business development strategy is needed, one of which is by applying an Islamic economic perspective. The Islamic economic perspective can provide guidelines in the development of a more sustainable and fair catfish seed business. This study applies qualitative research methods to explore the phenomena and problems in the catfish seed farming business in Tanggamus Regency. The focus was on understanding the challenges faced by farmers and relevant catfish seedling business development strategies. Through in-depth interviews and field observations, researchers gained insights into the Islamic economic strategies applied in the production, marketing and distribution of catfish seedlings. The results show that catfish seedling farming in Tanggamus Regency, Lampung, follows Islamic principles in its development strategy. Based on the values of honesty, sincerity, professionalism, good relations, holy intentions, as well as the obligations of zakat, infaq, and sadaqah, the business process is in accordance with the principles of Islamic Economics, which emphasizes ethics in running a business. The strategies implemented, such as the application of Good Breeding Practices (GBP) to ensure the quality of fish seeds, fair pricing, and distribution that expands the market without oppressing others, are a form of implementation of Islamic values in business practices.